2019
DOI: 10.2147/dddt.s225613
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy and Safety of Umbilical Cord Mesenchymal Stem Cell Therapy for Rheumatoid Arthritis Patients: A Prospective Phase I/II Study</p>

Abstract: Background: The traditional anti-inflammation disease-modifying anti-rheumatic drugs (DMARDs) have limited therapeutic effects in rheumatoid arthritis (RA) patients. We previously reported the safety and efficacy of umbilical cord mesenchymal stem cell (UC-MSC) treatment in RA patients that were observed for up to 8 months after UC-MSC infusion. The aim of this study is to assess the long-term efficacy and safety of UC-MSC along with DMARDs for the treatment of RA. Methods: 64 RA patients aged 18-64 years were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 30 publications
7
94
0
Order By: Relevance
“…Through the latter, MSC can regulate the immune response mediated by T cells, inhibit the production and function of various innate immune cells and play an anti-inflammatory role, regulate immunity and resist tissue injury. [ 23 ] Our previous study [ 18 ] has shown that UC- MSCs therapy for RA can reduce and alleviate the clinical symptoms of RA, and there is no significant change in human blood routine indicators, which showed good safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the latter, MSC can regulate the immune response mediated by T cells, inhibit the production and function of various innate immune cells and play an anti-inflammatory role, regulate immunity and resist tissue injury. [ 23 ] Our previous study [ 18 ] has shown that UC- MSCs therapy for RA can reduce and alleviate the clinical symptoms of RA, and there is no significant change in human blood routine indicators, which showed good safety.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous study, [ 18 ] the 28 joint disease activity score (DAS 28), the health assessment questionnaire (HAQ)score and RA clinical remission standard (ACR standard) were recorded 1 year before and after treatment. [ 19 ] The erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), rheumatoid factor (RF), and anti-cyclic citrullinated peptide antibody (Anti-CCP) were detected pretreatment and 1 year after treatment.…”
Section: Methodsmentioning
confidence: 99%
“…In the most recently published study, the umbilical cord mesenchymal stem cells (UC-MSCs) were used as a therapy for rheumatoid arthritis patients [41]. 64 patients received intravenously 40 ml of UC-MSCs suspension (2 × 10 7 cells/20 ml) along with disease-modifying anti-rheumatic drugs (DMARDs) and the results were assessed after 1 year and 3 years.…”
Section: The Possible Application Of Umbilical Cord Stem Cellsmentioning
confidence: 99%
“…After 3 years post treatment the effects of the therapy with UC-MSCs combined with DMARDs maintained, and included: reduced levels of RF, CRP, ESR and anti-CCP, lower HAQ and DAS28 scores and general alleviation of rheumatoid arthritis symptoms. It was suggested that UC-MSCs regulated patients' autoimmune tolerance, resulting in quality of life improvement [41]. With regards to arthritic disease treatments, it was also suggested that utilizing the secretome of these cells would be beneficial.…”
Section: The Possible Application Of Umbilical Cord Stem Cellsmentioning
confidence: 99%
“…2). Indeed, MSCs have shown success in the treatment of systemic lupus erythematosus [8], rheumatoid arthritis [9], type 1 diabetes mellitus [10], multiple sclerosis [11], liver failure associated with hepatitis B virus [12], ulcerative colitis [13], dacryoadenitis [14], Sjögren's syndrome [15], and systemic scleroderma [15]. A very recent example is the co‐administration of MSCs with pancreatic islets in immunocompetent type 1 diabetic wild‐type mice.…”
Section: Mscs For the Treatment Of Immune Pathologiesmentioning
confidence: 99%